Analysis of Adverse Drug Reactions Combination of Zidovudine, Lamivudine, and Nevirapine Drugs in the Treatment of HIV/AIDS Patients in a Denpasar District Hospital - Udayani, Ni Nyoman Wahyu; Dewi, Putu Intan Candra (Budapest International Research and Critics University, 2021)
HIV/AIDS is a disease caused by infection with the Human Immunodeficiency Virus (HIV). Antiretroviral therapy is used for treatment. The three most commonly used combination antiretroviral regimens are zidovudine, lamivudine, and nevirapine. The problem that arises from the use of antiretroviral drugs is the emergence of adverse drug reactions (ADR). The purpose of this study was to identify and analyze the incidence of adverse drug reactions from the use of combination antiretroviral drugs in the treatment of HIV/AIDS patients in a Denpasar district hospital. This study is a descriptive study with prospective data collection on the patient's medical record. The sampling technique in this study uses a non-probability technique (Purposive Sampling). This study involved 102 patients. The results obtained were descriptive analysis for patient demographic data, duration of therapy and adverse drug reactions that occurred. The results showed that there was an adverse drug reaction in 50% of patients who used a combination of antiretroviral drugs zidovudine, lamivudine and nevirapine. The longest duration of ARV therapy in one of the hospitals in Denpasar Regency was the age > more than 2 years to 4 years, which was 33.3%. The types of ADR that occurred were nausea/vomiting (25 events), skin rash (23 events), headache (11 events), lethargy/fatigue (6 events), fever (6 events), muscle pain (5 events), diarrhea (4 events), neuropathy (2 events), anemia (2 events), and the least is nail hyperpigmentation (1 event).